Results of the research of onion in the annual culture in the conditions of the Priobskaya zone of the Altai Territory - S. V. Zharkova; E. V. Shishkina (Овощи России)
Relevance. In the Western Siberia conditions bulb onion is grown mainly from onion sets. With this method of cultivation, large costs are spent on growing and storing the onion sets. In this regard, the cultivation of it through the seeds is of particular importance. This problem has not been studied enough in Priobskaya zone of Altai Territory conditions.Materials and methods. In our research, we studied the influence of cultivation conditions on the formation of economically valuable traits of varieties and a hybrid of bulb onion grown by sowing seeds in the ground in Priobskaya zone of Altai Territory. Three varieties were taken as objects of research: Odnoletniy Sibirskiy, Zolotnichok, Odintsovets, and one Candy F1 hybrid.Results. On average, over the years of research on early maturity, the standard Odnoletniy Sibirskiy variety (87-88 days) showed itself to be the most early maturing. Candy F1 hybrid can be used as a source of early green mass. Leaf regrowth was the earliest of all onion samples studied. The largest leaf apparatus in the conditions of Priobskaya zone of Altai Territory is formed by the varieties Odintsovets (4.1 pieces per plant) and Odnoletniy Sibirskiy (3.8 pieces per plant). The maximum bulb mass was formed by the Candy F1 hybrid (51.5 g). The Candy F1 hybrid also was distinguished by the highest yield in the group of the studied samples. The increase in total yield was 5.1 t/ha, marketable 2.4 t/ha in relation to the standard. The maximum marketability in the experience was in the standard (80.9%).